International Organizations and Ethnic Conflict - Esman, Milton J.; Telhami, Shibley Z. (Cornell University Press, 2019)
From Rwanda to Somalia to the former Yugoslavia, one feature of the post-Cold War world has become dreadfully clear. Ethnic conflicts are escalating, and with them demands for international intervention. But legally most ethnic conflicts are "internal" matters. How are international organizations, their resources stretched woefully thin, to know when intervention is appropriate or possible? This volume addresses the changing nature of relations between war-torn multiethnic states and international organizations, particularly the United Nations and its agencies.Are the established norms that limit intervention in ethnic conflicts adequate to contemporary conditions? Can international organizations meet the increasing demand? If not, what are the consequences of the disparities between established norms, current capabilities, and expanding expectations--and how might these disparities be narrowed? The contributors explore the desirability and potential effectiveness of international interventions in ethnic conflicts. Detailed studies of two specific cases of severe and violent tensions, in Lebanon and Yugoslavia, complement the general discussion with particular insights into the risks and exigencies of international attempts to manage ethnic civil war.A deeply thoughtful overview of one of the most pressing and perplexing issues confronting the world today, this volume clarifies the changing role of international organizations in an increasingly fragmented world.